Towards a Better Understanding of Foreign Workers' Satisfaction with Cooperative Health Insurance: The Role of Service Characteristics, Financing, Choice of Plan and Customer Knowledge - Mubarak Aldosari; Yusnidah Ibrahim; Norlida Binti Abdul Manab; Ebrahim Mohammed Al-Matari; Eqab Aiyadh Alotaibi (International Review of Management and Marketing, 2016)
This study explored the relationships among several antecedent factors, namely service characteristics, financing and choice of plan and foreign workers' satisfaction with cooperative health insurance (CHI). The study also hypothesized that customer knowledge situation would moderate the relationships among these antecedent factors and foreign workers' satisfaction with CHI. Drawing from a sample of 384 expatriates in Saudi Arabia, we found that service characteristics were positively related to foreign workers' satisfaction with CHI. We also found evidence regarding the relationship between CHI financing and foreign workers' satisfaction with CHI. Similarly, CHI choice of plan was found to be a significant predictor of foreign workers' satisfaction with CHI. Importantly, we predicted that perceived antecedent factors would each interact with customer knowledge in explaining foreign workers' satisfaction with CHI, such that this relationship would be stronger when customer knowledge situation is high and weaker when customer knowledge situation is low. Accordingly, the results generally supported our predictions.